Sowing machines and systems based on the elements of fluidics - Aulin, V.; Chernovol, M.; Pankov, A.; Zamota, T.; Panayotov, K.; Аулін, В. В.; Черновол, М. І.; Панков, А. О.; Замота, Т. М. (INMA Bucharest, 2017)
On the basis of the research results it is established that to increase the productivity and quality, as well as to reduce the work intensity of planting machines it is necessary to unite the metering and timing system on one principle – the principle of discrete action. The rational basis for this is using of control and power fluidic devices, and active distribution of pneumatic devices and pneumatic power systems. On this basis, pneumatic seeding systems on the row and one grain sowing were developed, which also allows distributing seeds differentially when this seeding technology is used for precision farming. На підставі результатів досліджень встановлено, що для підвищення продуктивності і якості, зниження енергоємності роботи посівних машин необхідно об'єднання висівного апарату і системи синхронізації на одному принципі – дискретної дії, а раціональною основою для цього є застосування керуючих і силових струменевих елементів, а також активних пневматичних розподільних пристроїв і пневматичної системи живлення. Виходячи з цього, розроблено пневмоструминні висіваючі системи для рядової і однозернової сівби, що також дозволяють диференційовано розподіляти насіння при сівбі по технології точного землеробства.
Висівні машини та системи на основі елементів пневмоніки
Keywords: pneumonics; fluidics; stream element; sowing system